Mixed cropping of Medicago ruthenica-Bromus inermis exhibits higher yield and quality advantages in the Longxi loess plateau region of Northwest China - Wei, Kongtao; Xiang, Hang; Liu, Yaofeng; Zhang, Xuanming; Yu, Xiaojun (Frontiers in Sustainable Food Systems, 2024)
Medicago ruthenica is a promising leguminous forage crop due to its lack of saponins, which prevents bloat in livestock from excessive consumption. Legume/grass mixed cropping is an effective forage planting method widely used in agricultural and pastoral regions. However, there is a lack of research on using legume-grass mixed cropping to establish perennial, high-yield, and high-quality cultivated grasslands in the Longxi Loess Plateau. This study conducted a legume/grass intercropping experiment in the Longxi Loess Plateau region of northwestern China, using Medicago ruthenica and Bromus inermis. Experimental plots were established in 2021, with field sampling and laboratory analysis starting in 2022 and 2023, respectively. The research aimed to investigate the effects of intercropping Medicago ruthenica with Bromus inermis on forage yield and quality, and to determine the optimal intercropping ratios. The experiment tested various intercropping ratios of Medicago ruthenica and Bromus inermis in the fall (2:8, 3:7, 4:6, 5:5, 6:4, 7:3, 8:2), with sole crops of each species serving as controls. Results showed that, in the second and third years of mixed cropping, the forage yield under mixed cropping treatments was significantly higher than that of Medicago ruthenica and Bromus inermis monoculture, with increases of 40.89–70.88% and 13.97–38.22% in the second year, and 131.91–199.13% and 44.06–85.82% in the third year. When the legume proportion in the mixed cropping system was around 30%, competition between the two forages reached equilibrium, demonstrating the benefits of mixed cropping. The crude protein and ether extract content of mixed forage were significantly higher than those of monoculture, while the neutral detergent fiber and acid detergent fiber contents were significantly lower, indicating a higher feeding value for the mixed forage. The legume proportion was a key factor influencing the yield of mixed forage. In conclusion, a mixed planting ratio of Medicago ruthenica and Bromus inermis at 3:7 resulted in higher yield and nutritional quality, making it an optimal ratio for establishing cultivated forage fields in the Longxi Loess Plateau.